HUBUNGAN PERILAKU KONSUMSI MAKANAN DENGAN STATUS GIZI PNS BAPPEDA KABUPATEN LANGKAT TAHUN 2015 - Nia Sylviana Junaz; Jumirah .; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Food consumption behaviour is the factor which affect nutritional status. Bad food consumption behaviour and less physical activity causes disturbed body metabolism so that can cause nutritional status becomes unfavorable. Food consumption in working adults should be adjusted with bodi’s to determine requirement and employment. The purpose of this research was the correlation between food consumption behaviour with nutritional status of civil servants in the BAPPEDA Langkat District. Types of this research was analytic by cross sectional design. Population of this research was 46 people The samples taken as many as 46 people by total sampling methods. Knowledge and balanced nutrition attitude of civil servants indicated by using questionnaires, while food arrangements, food frequency and quantity of carbohydrate, protein and fat intake indicated by using 24 hour recall and food frequency’s form. While, to see the correlation between food consumption behaviour with nutritional status of civil servants in the BAPPEDA Langkat District was used Pearson correlation test with confidence level as many as 95%. The result of research showed that civil servants in the BAPPEDA Langkat District have knowledge and balanced nutrition attitude was in moderate category, each of whices was 58,7% and 50,0%. Food consumption based on food arrangements was incomplete category as many as 76,1%. Frequency of vegetables and fruits average consumption was rarely, each of whices was 59,6% and 69,0%. The quantity of carbohydrate, protein and fat intake that consumed by civil servants in the BAPPEDA Langkat District was over, each of whices was 58,7%, 56,5% and 50,0%. The result of pearson correlation test indicates that there was correlation between knowledge balanced nutrition with attitude (p=0,047), food consumption (food arrangements, quantity of carbohydrate, protein and fat ) with nutritional status, each of whices was (p=0,043, p=0,045, p=0,004 and p=0,001). Based on the result of research suggested to civil servants in order to increase consumption of fruits and vegetable for stay fitness and healthy. Key words : food consumption behaviour, nutritional status, civil servant